Elucidating the action mechanisms of silicon in the mitigation of phosphorus deficiency and enhancement of its response in sorghum plants - Silva, José Lucas Farias da [UNESP]; Prado, Renato de Mello [UNESP] (Taylor & Francis, 2021)
Phosphorus (P) is one of the most limiting nutrients in agricultural production and silicon (Si) application is a strategy used to improve phosphate nutrition in plants; however, the action mechanisms of Si remain poorly understood in sorghum plants, under P deficiency of sufficiency. This study aimed at evaluating whether the supply of Si via nutrient solution benefits sorghum plants cultivated under sufficiency of deficiency of P, and investigate the interaction between nutritional and physiological mechanisms involved. In a completely randomized design with six replicates, treatments were arranged in a 2 × 2 factorial scheme, characterized by P sufficiency or deficiency, in combination with the presence (1.5 mmol L−1) of absence of Si in the nutrient solution. The experiment was carried out in pots filled with sand. Plants cultivated without Si and under P-deficiency had a reduced accumulation of P in its aerial parts, which compromised its physiology and growth. The inclusion of Si via nutrient solution increased P accumulation and its use efficiency in sorghum plants, and led to a reduction in the electrolyte leakage and an increase in the relative chlorophyll index of leaves. Similarly, the production of phenolic compounds and the quantum efficiency of the photosystem II (Fv/Fm) were also benefited from Si inclusion, as well as the diameter of the stems, which was also augmented together with plants’ height and dry matter production in these plants cultivated under P deficiency and sufficiency.
Keywords: beneficial element; nutritional disorder; phosphorus; silicon; Sorghum bicolorL